Thermomechanical behavior of a CuAlBe shape memory alloy - Montecinos Espinoza, Susana de Los Angeles (2008)
The deformation of a Cu-11.4wt%Al-0.5wt%Be polycrystalline alloy induced by compressive stress at room temperature was analyzed. The different contributions to the total strain were considered and its evolution with the stress was examined. The macroscopic plastic limit was determined at around 600 MPa of stress and 8 % of strain. This strain is associated with induced martensite, which transforms to b phase with a flash heating. Higher stress-strain levels introduce irreversible strain, and it would correspond to plastic deformation of martensite. Slip dislocations make difficult the mechanically as well as the thermally b-martensite transformation, leading to an hyperstabilization effect.